45.0k views
5 votes
For f(x) = 3x - 12 and g(x) = 2x^2 + 7, find f(g(-5)).

For f(x) = 3x - 12 and g(x) = 2x^2 + 7, find f(g(-5)).-example-1
User Yiqing
by
5.7k points

1 Answer

0 votes

Answer:

159

Explanation:

To evaluate f(g(- 5)), first evaluate g(- 5) then substitute this value into f(x)

g(- 5) = 2(- 5)² + 7 = 50 + 7 = 57

f(57) = (3 × 57) - 12 = 171 - 12 = 159


User Curt Rand
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.